Simulation of Solar Energy Harvesting on a 25-Meter Electric Passenger Ferry - Cahyagi, Danang; Prasetyo, Naufal Abdurrahman; Siregar, Jansen Anugrah; Ferdinand, Floribertus Rio (International Journal of Marine Engineering Innovation and Research, 2025)
This study investigates the integration of a solar photovoltaic system on the passenger ferry E.V. Calestia operating along Manila’s Pasig River. The ferry, equipped with dual 400 kW electric motors and a battery bank of 1848 kWh, is supplemented by 20 solar panels installed on its top deck. Using a Simulink-based simulation model, the research estimates the power output and cumulative energy generation based on panel specifications, solar irradiance, and system efficiency. Results show a maximum instantaneous power output of approximately 3 kW during peak sunlight and a total weekly energy generation of around 150 kWh. These findings demonstrate the potential of solar power to enhance the ferry’s energy sustainability by reducing reliance on conventional charging and lowering emissions, thus promoting greener maritime transport solutions in urban river environments.